Academic Procrastination, Self-Esteem and Self-Efficacy in University Students: Comparative Study in Two Peruvian Cities - Uribe Hernández, Yrene Cecilia; Alegría Cueto, Oscar Fernando; Shardin-Flores, Nikita; Luy-Montejo, Carlos A. (International Journal of Criminology and Sociology, 2022)
The present study aims to determine the relationship between academic procrastination, self-esteem and self-efficacy in undergraduate students in two Peruvian cities. The population consisted of 13,767 students, from which a sample of 1,494 was extracted. The subjects were selected from eight universities: five private and one public, from the city of Metropolitan Lima; and two universities, one public and one private, from the city of Arequipa. The instruments used were the Academic Procrastination Scale (EPA), the Scale of Specific Perceived Self-Efficacy in Academic Situations (EAPESA) and the Rosemberg Self-Esteem Scale. The results allow us to conclude that, in terms of perceived effectiveness, the relationship is slightly higher in the city of Arequipa, reiterating this with respect to academic procrastination, where the relationship is also slightly higher. Finally, with regard to self-esteem, the trend continues to indicate a greater relationship in Arequipa